CTA and documentary microcomputing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
As part of its mission to train the agricultural information services of the ACP states, CTA organizes introductory courses in documentary microcomputing. These courses consist of two stages: firstly; an introduction to the basics of microcomputing,...